Factors Associated With Multiple Falls Among Elderly Patients Admitted to Emergency Department - (:unkn) unknown (TAIWAN SOC GERIATRIC EMERGENCY & CRITICAL CARE MEDICINE-TSGECM, 2017)
Background: Fall related injuries constitute a significant part of emergency department admissions of geriatric patients. Recurrent falls are also not uncommon. The aim of this study is to evaluate the factors that might be related with multiple falls among the elderly patients admitted to emergency department. Methods: The study was conducted between 1st May 2014 and 31 October 2014 at a tertiary education and research hospital in Istanbul, Turkey. All the patients over 65 years who admitted to emergency department due to falls were included. Patients and/or their relatives were asked to answer the questions searching for possible factors that may interfere with their multiple falls. Results: During the study period 308 patients over 65 years old admitted to emergency department. 51% were between 65 and 79 years old and 49% were >80 years old. The women constituted the 70.1% of the cases. The majority of the cases described the mechanism of injury as stumbling and fall (72.4%). Factors related with multiple falls were as follows: being between 65 and 79 ages, being physically active before the fall event, having chronic cardiovascular and neurologic diseases and being on benzodiazepine and SSRI medication. Conclusion: Physically active and relatively younger elderlies fall more frequently. As the most commonly described mechanism was stumbling and fall, the importance of environmental risk factors is emphasized. Patients with cardiovascular and neurological diseases should be further evaluated for increased fall risk and indications of benzodiazepines and SSRI's in elderly people should be well evaluated. Copyright (C) 2017, Taiwan Society of Geriatric Emergency & Critical Care Medicine. Published by Elsevier Taiwan LLC.
Keywords: elderly; falls; geriatric falls; emergency department; OLDER-ADULTS; RECURRENT FALLS; RISK; COMMUNITY; PREVENTION; INJURIES; PEOPLE; INTERVENTIONS; EPIDEMIOLOGY; MORTALITY